LIOPHILIZATION OF THE SURFACE OF MONODISPERSE SPHERICAL SILICA PARTICLES AND SYNTHESIS OF OPAL PHOTON-CRYSTALLINE STRUCTURES FROM LIOPHILE SUSPENSIONS - Serdobintseva V.V.; Kalinin D.V.; Sobolev N.V. (My University, 2007)
In natural conditions, some minerals (e.g., hydrophile colloidal clay minerals) form liophile colloidal suspensions, which are characterized by a low interphase surface energy σ (σ < βkT/4πr2, where β = 20 is the coefficient depending on the concentration of particles in suspension and r is the size of particles), a great affinity to disperse media, and the ability of spontaneous transition to the free disperse state. In contrast to liophobe colloidal systems, where σ >> βkT/4πr2, these minerals are thermodynamically stable. Amorphous silica has hydrophile properties when particles are 5–10 nm in size. However, the silica particles >50 nm in size behave as liophobe ones. Monodisperse spherical silica particles, MSSP (200–300 nm in size), which make up opal structures, are not dispersed spontaneously, and MSSP suspensions obtained by synthesis of opal with technique are liophobe materials. Their relative kinetic stability and some liophile-type properties are caused by the presence of a stabilizing electrolyte in the system and occurrence of the double diffusion layer of counterions around the negatively charged MSSPs.